Efficacy and tolerability of oral oxycodone and oxycodone/naloxone combination in opioid-naïve cancer patients: a propensity analysis - Lazzari, Marzia (Drug Des Devel Ther, 2015)
BACKGROUND: World Health Organization step III opioids are required to relieve moderate-to-severe cancer pain; constipation is one of the most frequent opioid-induced side effects. A fixed combination, prolonged-release oxycodone/naloxone (OXN), was developed with the aim of reducing opioid-related gastrointestinal side effects. The objective of this study was to compare the efficacy and safety of prolonged-release oxycodone (OXY) alone to OXN in opioid-naïve cancer patients with moderate-to-severe pain. METHODS: Propensity analysis was utilized in this observational study, which evaluated the efficacy, safety, and quality of life. RESULTS: Out of the 210 patients recruited, 146 were matched using propensity scores and included in the comparative analysis. In both groups, pain intensity decreased by ≈3 points after 60 days, indicating comparable analgesic efficacy. Responder rates were similar between groups. Analgesia was achieved and maintained with similarly low and stable dosages over time (12.0–20.4 mg/d for OXY and 11.5–22.0 mg/d for OXN). Bowel Function Index (BFI) and laxative use per week improved from baseline at 30 days and 60 days in OXN recipients (−16, P<0.0001 and −3.5, P=0.02, respectively); BFI worsened in the OXY group. The overall incidence of drug-related adverse events was 28.9% in the OXY group and 8.2% in the OXN group (P<0.01); nausea and vomiting were two to five times less frequent with OXN. Quality of life improved to a significantly greater extent in patients receiving OXN compared to OXY (increase in Short Form-36 physical component score of 7.1 points vs 3.2 points, respectively; P<0.001). CONCLUSION: In patients with chronic cancer pain, OXN provided analgesic effectiveness that is similar to OXY, with early and sustained benefits in tolerability. The relationship between responsiveness to OXN and clinical characteristics is currently being investigated.